2012
DOI: 10.3844/ajptsp.2012.154.163
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Vitamin E

Abstract: Drugs and some chemical agents are known to induce hepatotoxicity in humans which is of great concern to clinicians. Chemical agents are been screen daily for their hepatoprotective properties. Among these chemical agents is vitamin E which has drawn wide attention due to it reported hepatoprotective property as reported by researchers. This study collected and evaluated reports to ascertain the hepatoprotective effect of vitamin E. A comprehensive literature review on the hepatoprotective property of vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
5
0
4
Order By: Relevance
“…Moreover, supplementation of diet with vitamin E protected sperm DNA from oxidative stress of free radicals (Jedlinska et al, 2006) in rats and increased the activity of antioxidant enzymes involved in the removal of ROS generated by cell metabolism (Caetano et al, 2013). In addition to Adikwu and Nelson (2013) reported that vitamin E exhibited hepatoprotective effect and decreased oxidative stress in the liver manifested through decrease in microsomal lipid peroxidation. It normalized levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, serum bilirubin, glutathione superoxide dimutase, lactose dehydrogenase, malondialdehyde and improved histopathological changes in the liver induced by chemical agents.…”
Section: Ajasmentioning
confidence: 99%
“…Moreover, supplementation of diet with vitamin E protected sperm DNA from oxidative stress of free radicals (Jedlinska et al, 2006) in rats and increased the activity of antioxidant enzymes involved in the removal of ROS generated by cell metabolism (Caetano et al, 2013). In addition to Adikwu and Nelson (2013) reported that vitamin E exhibited hepatoprotective effect and decreased oxidative stress in the liver manifested through decrease in microsomal lipid peroxidation. It normalized levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, serum bilirubin, glutathione superoxide dimutase, lactose dehydrogenase, malondialdehyde and improved histopathological changes in the liver induced by chemical agents.…”
Section: Ajasmentioning
confidence: 99%
“…Витамин E (альфа-токоферол, токотриенол) -жирорастворимый антиоксидант, известный как ингибитор перекисного окисления липидов [24,25]. С учетом данного свойства токоферол рассматривается как протектор при сердечно-сосудистых заболеваниях и используется при ишемической болезни сердца [26].…”
Section: гепатотоксичность витамина Eunclassified
“…Во многих исследованиях продемонстрированы индивидуальные особенности гепатотоксичности аюрведических и китайских трав, зеленого чая, гербалайфа, в том числе витаминов А и E [20][21][22][23]. Жирорастворимые витамины А и E чаще рассматриваются как антиоксиданты, которые тормозят реакции, предупреждающие образование свободных радикалов, повреждающих клеточные мембраны [24][25][26]. Однако на фоне нарушения режима приема или сбоя в гепатобилиарной системе они оказывают токсическое воздействие на печень [25][26][27].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For hepatoprotective properties, many chemical agents are screened. Vitamin E is a popular compound, regarded widely because of its documented hepatoprotective effect 14 . Due to this special property, Vitamin E has received extensive attention.…”
Section: Introductionmentioning
confidence: 99%